An evaluation of the response of a scintillation detector for estimating the radionuclide composition of a contaminated cloud - Klusoň, Jaroslav; Čechák, Tomáš; Kuča, Petr; Hůlka, Jiří (Applied radiation and isotopes, 2009)
We have made Monte Carlo calculations of the scintillation spectrometer response for the photon field from a cloud of contaminated air after selected scenarios of a nuclear power plant accident. Calculations (using MCNP5 code-X-5 Monte Carlo Team, 2005) were performed for 36 main energy lines of the expected radionuclides. The evaluated spectra enable us to simulate real composite spectra and their evolution in time, and to assess the applicability of a specific spectrometry system for a semi-qualitative and semi-quantitative analysis of the composition of the cloud.
Keywords: Radioactive Fallout; Equipment Design; Reproducibility of Results; Equipment Failure Analysis; Air Pollutants, Radioactive; reprodukovatelnost výsledků; Radioisotopes; scintilace - počítání; radioaktivní látky znečišťující vzduch; design vybavení; radionuklidy; analýza selhání vybavení; Scintillation Counting; Sensitivity and Specificity; senzitivita a specificita; radioaktivní spad